Tissue Expansion: Scalable and Isotropic Expansion of Tissues with Simply Tunable Expansion Ratio (Adv. Sci. 22/2019). Issue 22 (20th November 2019) - Park, Han‐Eol; Choi, Dongkil; Park, Ji Su; Sim, Changgon; Park, Sohyun; Kang, Sunah; Yim, Hyunsoo; Lee, Myungsun; Kim, Jaeyoun; Pac, Jinyoung; Rhee, Kunsoo; Lee, Junho; et al.
Abstract : In article number 1901673, Yan Lee, Sung‐Yon Kim, and co‐workers develop ZOOM, a new tissue expansion technique based on the hydrogel conversion reaction, to enable scalable and isotropic expansion of biological samples with easily tunable expansion ratio (up to eightfold). This method allows for simple and flexible expansion of a wide range of biological samples, from bacteria to human brain tissues, for super‐resolution imaging of samples with ordinary microscopes.